60 let študija ekonomskih in poslovnih ved (University of Maribor Press, 2019)
60 Years of Economics and Business Studies. The presented work presents a comprehensive view of the milestones and vision of the development and operation of the Faculty of Economics and Business. The monograph presents individual areas of work at the EPF, namely a brief presentation of the faculty and individual study programs today. Chairs and field of work of professional services are presented. The EPF has also progressed internationally lately, as evidenced by the accreditations and exchanges of students and staff. The research activity is presented with some achievements. Students at all levels of study are increasingly becoming involved. We also publish the scientific journal Our Economy. Contributors to the library co-facilitate the study and research process. The career center and the strategic world are influential in the development of our pedagogical work and student competencies.